Formation of low melting point binary systems comprising ketoprofen and an amide local anaesthetic - Tajber, Lidia (My University, 2021)
Liquid forms of active pharmaceutical ingredients, ionic liquids (ILs) and deep eutectic mixtures (DEMs), offer several potential benefits in respect to advancing pharmaceutical formulations. The aim of this study was to develop and characterise ILs/DEMs composed of two active molecules: ketoprofen (KET), as the acidic component, and a local anaesthetics (LA), lidocaine (LID), mepivacaine (MEP) or bupivacaine (BUP), which constituted the basic component. A mechanosynthetic approach was successfully applied to obtain LA-KET low melting systems. Composition/temperature phase diagrams were determined by differential scanning calorimetry. The amide LA-KET mixtures showed a eutectic behaviour during heating and formed viscous liquids upon quench cooling. Considering the quench cooled LA-KET mixtures, LA crystallisation was observed only in the LA-rich mixtures. LID, MEP and BUP formed disordered complexes with KET at an approximate 1:2 stoichiometry. Infrared spectroscopy studies revealed that the mixtures were composed mainly of hydrogen bonded acid and base molecules, but small amounts of carboxylate anions were detected. The formation of LA-KET complex not only suppressed the high crystallisation tendency of the LA molecules in the dry state, but also eliminated the crystallisation of KET and LA molecules induced by moisture, as revealed by dynamic vapour sorption studies.
PUBLISHED
Keywords: Mechanochemistry; Eutectic mixture; Ketoprofen; Lidocaine; Bupivacaine; Mepivacaine; Local anaesthetic